2013
DOI: 10.5653/cerm.2013.40.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of Obox4 is dependent on its homeobox domain

Abstract: ObjectiveOocyte-specific homeobox 4 (Obox4) is preferentially expressed in oocytes and plays an important role in the completion of meiosis of oocytes. However, the Obox4 expression pattern has not been reported yet. In this study, we investigated the subcellular localization of Obox4 using a green fluorescent protein (GFP) fusion expression system.MethodsThree regions of Obox4 were divided and fused to the GFP expression vector. The partly deleted homeodomain (HD) regions of Obox4 were also fused to the GFP e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This finding suggests that Sebox is certainly a significant regulator of ZGA, but it is not critical or exclusive because the expression levels of 5 out of 13 genes were not affected. SEBOX contains a homeodomain and may thus act as a transcription factor [ 8 , 26 , 27 ]. Indeed, a transcriptional activity assay confirmed a reduction of embryonic transcriptional activity after Sebox RNAi knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that Sebox is certainly a significant regulator of ZGA, but it is not critical or exclusive because the expression levels of 5 out of 13 genes were not affected. SEBOX contains a homeodomain and may thus act as a transcription factor [ 8 , 26 , 27 ]. Indeed, a transcriptional activity assay confirmed a reduction of embryonic transcriptional activity after Sebox RNAi knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The Obox4 protein is divided into three distinct regions: the N-terminal region, the central homeodomain (HD) region and the C-terminal region. Using a green fluorescent protein (GFP) fusion expression system, Park et al revealed that intact HD region of Obox4 which harbors the presumptive DNA-binding motif essential for its transcription factor activity, may be responsible for the nuclear localization of Obox4 [ 40 ].…”
Section: The Role Of Obox In Zgamentioning
confidence: 99%